Motivational crowding out effects in charitable giving: Experimental evidence - Stephan Müller; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
This paper tests motivational crowding out in the domain of charitable giving. A novelty is that our experiment isolates alternative explanations for the decline of giving such as strategic considerations of decision makers. Moreover, preference elicitation allows us to focus on the reaction of donors characterized by different degrees of intrinsic motivation. In the charitable-giving setting subjects donate money to the German "Red Cross" in two consecutive stages. The first dictator game is modified, i.e., donors face with equal probability an ex post reimbursement or a subsequent pay. The second game is a standard dictator game where we control for the decline of giving. We find that subjects with a high degree of intrinsic motivation, who received a reimbursement, reduce their donations more than four times as much as equally motivated individuals who did not experience a payment.
Keywords: D02; D03; C91; 330; Altruism; Dictator Game; Experiment; Motivational Crowd Out